Synthesis and Characterization of BaTi-xSnxO3 (x ≤ 0.40 ) System and its Composites - Ansaree, MD Jawed (IIT(BHU) Varanasi, 2017)
Abstract is available in content.
Keywords: Characterization of BaTi-xSnxO3 (x ≤ 0.40 ) System; Synthesis of BaTi-xSnxO3 (x ≤ 0.40 ) System